2022
DOI: 10.1021/acsaem.1c03480
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Enhanced Counter Electrode Materials for the Fabrication of Ultradurable Electrochromic Devices

Abstract: Electrochromic devices (ECDs) and especially electrochromic supercapacitors, where the real-time state of charge is indicated by the color, have a wide range of applications. However, to meet modern challenges, these devices should demonstrate exceptional charge–discharge durability. In this work, we demonstrate that electrochemical cycling stability of ECDs based on a monolayer of 4′-(4-pyridyl)-2,2′:6′,2″-terpyridine–iron­(II) complex that was covalently linked to the working electrode (WE) can be drasticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Previously, we have demonstrated that ECDs of the basic configuration (Figure 1A) often suffer from polarization of the CE leading to decomposition of the Li + gel electrolyte on the interface with CE. 25,26 Utilization of high surface area CE allows one to drastically slow down the rate of the decomposition of the solid-state EDCs during electrochemical cycling and, thus, provides access to ultradurable devices. 25,26 In this work, we examined and compared the long-term cycling durability performance of the double-side ECDs, ds-Fe4′T-S-ECD and ds-Nf-Fe4′T-S-ECD.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, we have demonstrated that ECDs of the basic configuration (Figure 1A) often suffer from polarization of the CE leading to decomposition of the Li + gel electrolyte on the interface with CE. 25,26 Utilization of high surface area CE allows one to drastically slow down the rate of the decomposition of the solid-state EDCs during electrochemical cycling and, thus, provides access to ultradurable devices. 25,26 In this work, we examined and compared the long-term cycling durability performance of the double-side ECDs, ds-Fe4′T-S-ECD and ds-Nf-Fe4′T-S-ECD.…”
Section: Resultsmentioning
confidence: 99%
“…The enhanced cycling stability, in this case, comes from the higher surface area of the CE that allows better ion distribution upon the formation of a double layer and reduces cell polarization by compensating for the charge at the WE. 25,26 Sealing together two Fe4′T/ITO NPs ECMs the way that they face each other using the gel electrolyte gives a symmetrical device. Because Fe4′T/ITO NPs ECM is colored in its native state, the traditional symmetric device architecture does not show a significant change in optical density.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These values are typical for the ferrous (Fe 2+ ) oxidation state. 24 It should be mentioned that even though the C 1s spectrum of the fresh bulk sample contains the same features as the initial bloodstain, the ratio of the (C-C) : (C-O and C-N) : (CvO and OvC-N) is equal to 47.8 : 13.6 : 10.3. The increase of the aliphatic carbon content on the surface of the bulk compared to the surface of the initial bloodstain indicates a different Paper Analyst protein content.…”
Section: Elemental Composition -Xpsmentioning
confidence: 97%
“…Electrochromic (EC) materials and electrochromic devices (ECDs) that show reversible color change upon application of a voltage have been widely used in a number of commercial and military applications, including energy-saving smart windows, flexible displays, , e-papers, , protective eyewear, , security, , energy storage devices, camouflage, and so on. In the past few decades, various types of materials have been established as EC materials, which can be classified into inorganic EC materials (various transition-metal oxides), organic EC materials (organic small molecules and polymers), and organic–inorganic hybrid EC materials (various metal–organic systems). Metallo-supramolecular polymers (MSPs) are generally considered as organic–inorganic hybrid EC materials because these polymers are typically synthesized by 1:1 complexation between organic ligands and metal ions. ,, Since Higuchi et al demonstrated the EC color change of MSP prepared from 1,4-bis­(2,2′:6′,2″-terpyridine-4′-yl)-benzene as a ditopic ligand and the Fe­(II) ion as the metal ion, many MSPs have been developed using bisterpyridine ligands and various metal ions like Fe 2+ , Co 2+ , Ru 2+ , Os 2+ , Cu 2+ , and so forth. , These monometallic MSPs have attracted great research attention for EC applications because of their interesting physical and optoelectronic properties like solution processability, high color contrast, fast response times, good coloration efficiency, and high durability.…”
Section: Introductionmentioning
confidence: 99%